Improvement in dispersement and agglomeration properties for carbon nanotube ink - Abdul Aziz, Nur Haziqah (2021)
Carbon nanotubes (CNTs) are developing in flexible, stretchable and sensitive electronic technologies for decades because of their impressive properties and performance in electrical and mechanical which are almost similar to metal. However, some of the current methods are costly as well as have issues with dispersion which will cause agglomeration and sedimentation of the nanotubes. This study aims to produce improved dispersion of CNT-polymer conductive nano- ink for printing technology without agglomeration and sedimentation issues. The functionalized MWCNTs is dispersed in isopropyl alcohol (IPA) solution and compared with other organic solvents such as methanol, ethanol, acetone, chloroform and Tetrahydrofuran (THF) using Raman spectroscopy, Fourier Electron Scanning Electron Microscopy (FESEM), and current-voltage (I-V) characterisations. The conductive ink is synthesised via ultrasonication and magnetic stirring. Eight samples are prepared for various conditions which include the presence of ethylcellulose, types of chitosan and concentration of MWCNTs. The characterization analyses such as Energy Dispersive X-Ray Analysis (EDX), FESEM, Fourier Transform Infrared Spectroscopy (FTIR), Raman spectroscopy, rheological measurement via rheometer, thermogravimetric analysis (TGA), Ultraviolet-Visible (UV-VIS), and electrical testing’s using 4-point probes as well as 2-point probes. EDX results show that the weight percentage of the Carbon (C) atom decrease with the presence of ethylcellulose. Meanwhile, the FESEM images show that the presence of ethylcellulose prevents the formation of nanotubes bundles. However, the higher concentration which is 5 mg/ml gives the better structure of nanotubes. The Raman study shows that the presence of cellulose increased the Peak Intensity Ratio for the carbon defect. The ethylcellulose also increased the viscosity of the conductive nano-ink, 11.13 mPA which is still in the range of the viscosity of commercial ink. Though the presence of ethylcellulose reduced the conductivity of the nano-ink, it successfully prevents the formation of the ‘coffee ring’ effect. Among all samples, Sample 7, the high concentration which is 5mg/ml with ethyl celluloses and chitosan solution is chosen as the best sample with better performance, stable and optimum conductivity on the glass which are in the range of 1.52x 10−01-01 to 2.15x 10−01. .